Seismic Vulnerability Assessment in Non-Engineered Dwellings Using RVS Methods and Its Validation with a Quantitative Approach - Adriano, Eloim (2025)
This research presents an analysis of seismic vulnerability in dwellings built without engineering criteria, aiming to determine their levels of vulnerability. Rapid Visual Screening (RVS) methods, such as those proposed by FEMA P-154 and developed by INDECI, were employed to assess the vulnerability of 20 dwellings. Additionally, a quantitative validation was conducted on two of thesed wellings using parameters like lateral drift to complement the qualitative analysis. The results obtained through FEMA P-154 indicate that 50% of the dwellings exhibit a "Very High" level of vulnerability, 45% a "High" level, and 5% a "Low" level. Meanwhile, the INDECI method classifies 45% of the dwellings as having "Very High" vulnerability and 55% as "High." The quantitative evaluation of lateral drift showed that Dwelling 1 and Dwelling 2 experienced excessive drift values of 0.006979 and 0.004624, respectively, classifying both as "vulnerable" to seismic events. When comparing the qualitative methods (FEMA P-154 and INDECI) with the quantitative method (lateral drift), slight discrepancies were identified in the assigned vulnerability levels, although they maintained a close correlation. While the qualitative methods indicated high and very high vulnerability, the quantitative method classified them as "Vulnerable." Despite these differences, the results converge in highlighting the high susceptibility of the analyzed dwellings to seismic events. These findings emphasize the need to prioritize structural reinforcements to reduce seismic risk levels in the evaluated area.